Occurrence of mental disorders in nonspecific inflammatory boweldiseases: a primary or secondary problem in relation to the biologicaltherapy used? - Olesiak, Mateusz; Stelmach, Ewa (Current Problems of Psychiatry, 2025)
Introduction: Nonspecific inflammatory bowel diseases include Crohn’s disease (CD) and ulcerative colitis (CU – colitis ulcerosa), which are chronic diseases characterized by periods of exacerbation and remission. Extraintestinal complications caused by the disease and the applied treatment, mainly steroid therapy, constitute a predisposition to infections and mental disorders such as depressive disorders with apathy, slowness of movement or agitation, and even manic syndromes. Aim and method: The aim of this study was to review the literature on the occurrence of primary and secondary mental disorders in the course of inflammatory bowel diseases. The literature in the Google Scholar database was reviewed using the following keywords: colitis ulcerosa, Crohn disease, depression, mental disorders, inflammatory bowel disease. The time descriptors 2011-2021 were also used. Conclusions: The review of epidemiological studies shows that the most common mental disorders in nonspecific inflammatory bowel diseases are anxiety and depression disorders. The effect of steroid therapy on the development of mental disorders is equally significant. Most of the available empirical data relating to corticosteroids confirm the correlation between the drugs and depressive symptoms, and other psychiatric effects, including mania and psychosis. Summary: As with most chronic diseases, the prevalence of anxiety and depression disorders is higher in nonspecific inflammatory bowel diseases than in the general population.